THE EFFECT OF SPECIAL EXERCISES USING SOME ASSISTIVE TOOLS IN DEVELOPING AGILITY AND ACCURACY OF SCORING WITH THE INSIDE OF THE FOOT FOR FOOTBALL PLAYERS UNDER (20) YEARS OLD - Asst.Lect. Abbas Majid Rashid (Proximus Journal Publishing, 2025)
The research aims to prepare special exercises using some tools to help develop agility and scoring accuracy with the inside of the foot for football players under 20 years old, as well as to identify the effect of special exercises using some tools to help develop agility and scoring accuracy with the inside of the foot to single out a sample. Search. To achieve the goal, the researcher used the experimental method with pre-test and post-test for suitability) with the research problem, and the research community consisted of Baghdad clubs for players under (20 years old) for Iraqi youth clubs, numbering (16) clubs, The total number of players is (430) players, which represents (100%) of the number of players. As for the research sample, it was represented by the players of Al-Hodood Sports Club for the youth category, who numbered (26) players, with a percentage of (6.05%). The research sample was chosen randomly by lottery road, The goalkeepers (4) were excluded, as were (4) players due to injury and non-compliance with the training units. (The researcher conducted the preand post-test for the individuals in the research sample, and the appropriate statistical treatments were conducted, The researcher concluded that the special exercises prepared by the researcher using some assistive tools had a positive effect in developing agility, and that the special exercises with the assistive tools used in developing agility had a positive impact on the accuracy of scoring from the inside of the foot, Gradually increasing the components of the training load, using appropriate repetitions in a undulating manner, had a positive and effective impact on improving agility, which was reflected in the accuracy of skill performance. The researcher recommends the need to (emphasize the use of assistive tools by coaches in the training process because of their positive impact on developing and developing the players’ abilities and potentials, as well as increasing their excitement factor when performing, Exercises for assistive devices must be applied to other age groups because of their positive role in developing physical and motor qualities and abilities, as well as similar studies and research to be conducted on other physical and motor qualities and skills in football, which the study did not address
Keywords: Auxiliary tools; scoring accuracy